Synaptic and extrasynaptic plasticity in glutamatergic circuits involving dentate granule cells following chronic N-methyl-d-aspartate receptor inhibition - He, Shuijin (American Physiological Society, 2013)
Chronic global N-methyl-d-aspartate receptor (NMDAR) blockade leads to changes in glutamatergic transmission. The impact of more subunit-selective NMDAR inhibition on glutamatergic circuits remains incomplete. To this end, organotypic hippocampal slice cultures were treated for 17–21 days with the high-affinity competitive antagonist d-aminophosphonovaleric acid (d-APV), the allosteric GluN2B-selective antagonist Ro25-6981, or the newer competitive GluN2A-preferring antagonist NVP-AAM077. Electrophysiological recordings from dentate granule cells revealed that chronic d-APV treatment increased, whereas chronic Ro25-6981 reduced, epileptiform event-associated large-amplitude spontaneous excitatory postsynaptic currents (sEPSC) compared with all other treatment groups, consistent with opposite effects on glutamatergic networks. Presynaptically, chronic d-APV or Ro25-6981 increased small-amplitude sEPSCs and AMPA/kainate receptor-mediated miniature EPSCs (mEPSC(AMPAR)) frequency. Chronic d-APV or NVP-AAM077, but not Ro25-6981, increased putative vGlut1-positive glutamatergic synapses. Postsynaptically, chronic d-APV dramatically increased mEPSC(AMPAR) and profoundly decreased NMDAR-mediated mEPSC (mEPSC(NMDAR)) measures, suggesting increased AMPAR/NMDAR ratio. Ro25-6981 decreased mEPSC(AMPAR) charge transfer and modestly decreased mEPSC(NMDAR) frequency and decay, suggesting downward scaling of AMPAR and NMDAR function without dramatically altering AMPAR/NMDAR ratio. Extrasynaptically, threo-β-benzyloxyaspartate-enhanced “tonic” NMDAR current amplitude and activated channel number estimates were significantly increased only by chronic Ro25-6981. For intrinsic excitability, action potential threshold was slightly more negative following chronic d-APV or NVP-AAM077. The predominant pro-excitatory effects of chronic d-APV are consistent with increased glutamatergic transmission and network excitability. The minor effects of chronic NVP-AAM077 on action potential threshold and synapse number are consistent with minimal effects on circuit function. The chronic Ro25-6981-induced downward scaling of synaptic AMPAR and NMDAR function is consistent with decreased postsynaptic glutamate receptors and reduced network excitability.